A review on the roles of ICT tools towards the development of fishermen - Omar, Siti Zobidah; Chhachhar, Abdul Razaque (TextRoad Publication, 2012)
This article assesses the role of the ICT in the development of fishermen. It discusses the issue of how ICT can help the fishermen in their daily fishing routine. ICT covers a number of tools and within the scope of this study, it emphasizes on the benefits and advantages of mobile phones, GPS, sonar, radio, television and internet. The results revealed that ICT gives significant improvement in their life. ICT have provided market access to fishermen for sell their produce and a better availability of up-to date information about weather and emergency. Additionally, ICT expands their markets and felt safe and more secure at sea. Similarly fishermen were close with their family and friends.